Comparison of anatomical locations of cutaneous melanoma in men and women: a population‐based study in France. (16th August 2014) - Chevalier, V.; Barbe, C.; Le Clainche, A.; Arnoult, G.; Bernard, P.; Hibon, E.; Grange, F.
<x xml:space="preserve">Abstract</x> What's already known about this topic? The predominance of melanomas on the trunk in men and on the lower limbs in women has been reported for a long time, and was recently found to decrease in some developed countries. Few population‐based studies have compared the precise location and side between the sexes. What does this study add? Women had more frequent melanomas on the lower limb, the hand and foot, and the central area and right side of the head and neck. Melanomas of the trunk, the peripheral area, and left side of the head and neck were more frequent in men. The distribution of foot melanoma differed between the sexes. Different patterns of ultraviolet and sun exposure suggest the usefulness of sex‐specific advice for melanoma prevention.